Screening for Obstructive Sleep Apnea Risk Using the STOP-BANG Questionnaire among Adults Attending a Tertiary Care Hospital in Eastern India: A Cross-Sectional Study - Vandana Majhi; Joenna Dev Ningombam; Joyeta Barick; Kiran S Kumar (National Journal of Community Medicine, 2026)
Background: Obstructive sleep apnea is a frequently overlooked sleep disorder associated with cardiovascular and metabolic morbidity that often remains underrecognized in routine clinical practice, making early risk assessment important. The objective was to assess OSA risk among adults using the STOP-BANG questionnaire (SBQ) and examine its association with selected sociodemographic and lifestyle factors. Methods: A cross-sectional study was conducted among 187 adults attending a tertiary care hospital in Eastern India, from September to November 2025. Participants were selected using systematic random sampling. OSA risk was assessed using the STOP-BANG questionnaire. Data were analyzed using descriptive statistics, Chi-square test and multivariable logistic regression. Results: The mean age of participants was 44.8 ± 17.5 years. Based on STOP-BANG scores, 14.4% were classified as high risk, 38.5% as moderate risk and 47.1% as low risk for OSA. Smoking and alcohol consumption were significantly associated with elevated OSA risk in bivariate analysis. However, after multivariable adjustment smoking remained independently associated with elevated OSA risk (AOR = 4.25; 95% CI: 2.09-8.66; p